COVID-19 Pandemic, Volunteering, and Well-Being: Volunteering's Role in Mitigating Depressive Symptoms, Loneliness, and Perceived Social Exclusion during the Pandemic - Nadiya Kelle; Mareike Bünning; Julia Simonson (Social Indicators Research, 2025)
The COVID-19 pandemic and its associated containment measures presented significant challenges in personal and social spheres, prompting the reorganization of prosocial activities. Despite the recognized buffering function of volunteering on well-being of older adults, it remains uncertain whether this function was maintained during the pandemic. Drawing on the framework of weak ties, this study investigates how starting, continuing, and stopping volunteering during the pandemic relate to changes in three aspects of well-being – depression, loneliness, and perceived social exclusion – compared to pre-pandemic times. It also examines differences in the buffering function of volunteering for people with lower levels of education compared to those with high levels of education. Utilizing data from the German Ageing Survey (DEAS), a representative study of the population aged 40 and above, three survey waves (2014, 2017, and winter 2020/21 when Germany experienced its second lockdown) were used to track changes across pre-pandemic and pandemic stages. Employing first-difference regressions, the study finds no general pandemic effect on depressive symptoms but identifies a negative impact on loneliness and perceived social exclusion. However, while the pandemic effect on loneliness did not differ between volunteer and non-volunteer groups, initiating volunteering protected against heightened feelings of social exclusion. This was particularly pronounced among new volunteers with lower levels of education. Continuous volunteers (with lower education) also tended to report lower social exclusion levels during the pandemic than non-volunteers. Theoretical and policy implications are discussed.
Keywords: 300; COVID-19; Volunteering; Well-being; Depressive symptoms; Loneliness; Perceived social exclusion; German ageing survey (DEAS)